Guided Inquiry Model Assisted with Interactive Multimedia Influences Science Literacy and Science Learning Outcomes - Dhia Suprianti; Munzil Munzil; Syamsul Hadi; I Wayan Dasna (Jurnal Ilmiah Sekolah Dasar, 2021)
The learning model during the pandemic is still teacher-centered so that most students experience problems in learning science. The purpose of this study was to measure the implementation of guided inquiry assisted by interactive multimedia on scientific literacy skills, learning outcomes of fifth-grade elementary school students. This research is a quasi-study with a non-randomized control group pretest-posttest design. The population of this study amounted to 60 students—the use of samples taken using non-randomized sampling. The experimental class has 30 students, and the control class has 30 students. The method used for data collection is an objective test. The results showed that: first, the scientific literacy ability of the experimental class was better than the control class based on statistical tests of 84.79 (very good) and 76.83 in the control class. Second, student learning outcomes in the experimental class were better than in the control class. It was concluded that the guided inquiry strategy using interactive multimedia had a significant impact on scientific literacy and student learning outcomes used in online science learning for elementary school students during the covid 19 pandemic. The research implication is that the inquiry learning model can be applied in the learning process because it can improve students' understanding.